First record of necrophagy by Scybalocanthon nigriceps Harold (Coleoptera, Scarabaeidae, Scarabaeinae) - Messas,Yuri F. (2012)
First record of necrophagy by Scybalocanthon nigriceps Harold (Coleoptera, Scarabaeidae, Scarabaeinae). The S. nigriceps specimen was observed making small cuts and removing portions of the carcass of a frog Haddadus binotatus (Spix) in February 24, 2011, in Serra do Japi, São Paulo State, Brazil. This note presents another record of necrophagy for Scybalocanthon.